Clinical and Bacteriological profile of Participants suspected with SBP in chronic liver disease coming in IGIMS Emergency, Patna - Kumar, Santosh; Anita; Nayan, Santosh Kumar; Kumar, Abhay; Singh, Siddharth (Student’s Journal of Health Research Africa, 2025)
Background Chronic liver disease (CLD) affects individuals of all ages, sexes, geographical locations, and ethnicities worldwide. Although the rate of progression and clinical course may vary, various etiological factors contribute to a similar clinicopathological pathophysiology in CLD. Objectives This study aimed to determine the bacterial profile, laboratory parameters, and clinical presentation of spontaneous bacterial peritonitis (SBP) and assess how these factors influence the outcomes of patients with CLD. Materials and Methods This retrospective, cross-sectional, observational study was conducted at Indira Gandhi Institute of Medical Sciences (IGIMS), Patna, Bihar, India, over a period of 18 months. A total of 160 patients were enrolled in the study. Case records of patients aged 18 years and older, diagnosed with SBP, were retrieved from the hospital’s electronic database and included in the study. Results Relevant gram-positive and gram-negative bacteria were identified in ascitic fluid and blood samples. Total leukocyte count, creatinine, bicarbonate, and direct bilirubin levels were found to be significantly associated with patient outcomes, including discharge against medical advice (DAMA), mortality, and successful discharge (p-value < 0.001). Among the patients, 16 (10%) had a history of SBP, and approximately 120 (75%) had not received antibiotics in the previous three months. Conclusion This study provides valuable insights into the clinical characteristics, laboratory findings, and bacterial profile of SBP in CLD patients. These findings highlight the importance of a multidisciplinary approach to SBP management and contribute to the growing body of knowledge on the condition. Recommendations The results of our investigation highlight the need for further research on geographical variations in the bacterial profile and clinical presentation of SBP, as well as the development of early diagnostic techniques and appropriate treatment plans.